THE DEVELOPMENT OF INTERACTIVE LEARNING MEDIA WITH MIND MAP CONCEPT IN VIDEO PROCESSING SUBJECT - Manurung, Desy Cobena (IJIE (Indonesian Journal of Informatics Education), 2020)
This research aims to create an interactive learning media with mind map concept in Video Processing subject Method used in this research was research and development with 5 steps, (1) problem and potency analysis, (2) data collection, (3) product design, (4) design validation, and (5) design improvement. Media’s advisibility, which had developed,  in percentage are 89% from media expert, 92% from material expert, 85% from users (limited) and 87% from users (expanded). It can be concluded that the design of learning media is “very appropriate”.The benefits of the learning media are: (1) interactive and fun, (2) equipped with videos tutorial, (3) equipped with exercises which able to scored and able to see the correct answers.